Impact of Rationality and Behavioural Factors on Investors Decision Making in the Pakistan Stock Exchange - Muhammad, Asif (2023)
This study has explored the impact of rationality, behavioral and demographic factors on the investors decision making at Pakistan Stock Exchange (PSX). The present study has also investigated correlation between rationality and behavioral factors while making financial decision-making at stock exchanges. The study has used descriptive research design based on survey method to collect data and test the hypotheses. A structured questionnaire developed through literature review and validated through pretesting and seeking experts’ opinion, has been distributed through convenience sampling. The population framework is consisted of small individual investors making investments at the six floors of PSX. The collected data is analyzed using descriptive and inferential statistics in SPSS v23.0 in addition to structural equation modelling (SEM) through AMOS v22.0. The findings reveal that rationality (Problem identification, searching information and evaluating alternatives) and behavioral factors (overconfidence, herd behavior and anchoring) have statistically significant positive impact on the small investors’ investment decision making. Correspondingly, the results of path analysis have confirmed a significant positive impact of the factors of rationality including “demand identification (β= 0.31), searching information (β=0.41) and evaluating alternatives (β=0.13)” on in investors’ investment decision making at p<0.001. Similarly, the findings of path analysis have also exhibited a significant positive impact of behavioral factors including “overconfidence (β=0.32) herd behavior (β=0.31) and anchoring (β=0.49) on investors’ investment decision making at p<0.001. Moreover, the results have also determined a significant negative impact of gender and a significant positive impact of education on the investors’ investment decision making at p<0.001. The present study has also determined significant positive correlation between rationality (problem identification, searching information and evaluating iiialternatives) and behavioral factors (overconfidence, herd behavior and anchoring). This is a baseline study in Pakistan to understand the rationality and behavioral factors involved in investment decision making of small investors at the floors of PSX. The findings may be helpful for the individual and institutional investors to be aware of different factors involved and develop “adaptive toolboxes” for making rational and consistent investment decisions at PSX.